LENS and NoPin (NP) ensemble means for apparent oxygen utilization (AOU), anthropogenic and preindustrial carbon, pCFC-12, and ideal age from Olivarez et al. (2023) - Holly C. Olivarez; Nicole S. Lovenduski; Yassir A. Eddebbar; Amanda R. Fay; Galen A. McKinley; Michael N. Levy; Matthew C. Long (Zenodo, 2023)
Manuscript title: "How does the Pinatubo eruption influence our understanding of long-term changes in ocean biogeochemistry?" Authors:Holly C. Olivarez 1,2 , Nicole S. Lovenduski 2,3 , Yassir A. Eddebbar 4 , Amanda R. Fay 5 , Galen A. McKinley 5 , Michael N. Levy 6 , and Matthew C. Long 6 Affiliations: 1 Department of Environmental Studies, University of Colorado, Boulder, CO, USA 2 Institute of Arctic and Alpine Research, University of Colorado, Boulder, CO, USA 3 Department of Atmospheric and Oceanic Sciences, University of Colorado, Boulder, CO, USA 4 Scripps Institution of Oceanography, University of California San Diego, La Jolla, CA, USA 5 Columbia University and Lamont-Doherty Earth Observatory, Palisades, NY, USA 6 Climate and Global Dynamics Laboratory, National Center for Atmospheric Research, Boulder, Colorado, USA LENS and No Pinatubo (NoPin in manuscript,NP in file names) CESM ensemble means for apparent oxygen utilization (AOU), anthropogenic and preindustrial carbon, p CFC-12, and ideal age along GO-SHIP transects akin to A16N , A16S , P16N , P16S , SO4I , SO4P . The CESM source code is freely available at http://www2.cesm.ucar.edu . The model outputs described in this paper can be accessed at www.earthsystemgrid.org . Anthropogenic carbon is calculated by subtracting DIC_ALT from DIC. Preindustrial carbon is labeled DIC_ALT.